Lectora inspire software development in the learning of pencak silat - Aref Vai; Fitri Agung Nanda; Deny Pradana Saputro; Ramadi; Muhammad Imam Rahmatullah (UIR Press, 2021)
Entering the 4.0 era, innovation and learning development are needed as well in the world of refereeing, development is intended to make it easier and help to reduce mistakes in leading matches. This study aims to develop lectora inspire which will be used in martial art refinement. This type of research is a research and development (R&D) research. The subjects of this study use a small scale with a total of 10 students from the Department of Physical Education, Health and Recreation, Faculty of Teacher Training and Education, Universitas Riau. Meanwhile, the analysis technique used in this research is descriptive quantitative. The results of the research on the development tools of lectora inspire on martial art refinement are good, this is explained from the results of the validation of the content/material aspects with an average score of 4.29, the learning aspects are categorized as good with an average score of 4.34, the programming aspects and the media aspects have good categories. From the results of small group trials conducted by 10 subjects, data are obtained and it is concluded that the Lectora Inspire application is in good category with an average score of 4.32 and is able to be applied in learning martial art refinement. These results are intended to make it easier and help to reduce errors in the referee's assignment when serving on a small scale. Based on the results of this study, it can be concluded that the development of learning media for refereeing martial art by utilizing lectora inspire is suitable for use as a medium in learning audio-visual based martial art on a small scale.